Foreign Accent and Levels of Analysis: Interference between English and Croatian - Josipović Smojver, Višnja (2010)
This work deals with the roles of the various levels of analysis in the creation of foreign accent. This is done with reference to and through the comparison of one pair of languages: Croatian and English. With the process of globalisation English has become indispensable in Croatia, as well as in the rest of Europe. Experience with analysing what is known as Croglish may be useful for linguists interested in the influence of other foreign languages, particularly those typologically similar to Croatian with respect to any aspect of phonology.
Projekt MZOS
ENG